Preference for male child among married adults in rural and urban field practice areas of Narayana Medical College, Nellore, Andhra Pradesh, India - Vardhan, Y. Vishnu; Rao, D. Srinivas (International Journal Of Community Medicine And Public Health, 2020)
Background: Reduction of national fertility levels was directly proportional to the preference of male child in many families in India. We conducted this study on 214 married adults, in both sexes to find out whether this strong preference still exists in this decade or not, and if it does what could be the reasons. Methods: A community based cross-sectional study done by face to face interviews using a semi-structured questionnaire containing both qualitative and quantitative variables, among 214 married adults. Results: Upon analysing the results, we identified that higher son preference (61.23%) is seen in many rural families, and is strongly associated with low socio-economic status, literacy rate and caste. The reasons by which these families prefer male child were also broadly categorized and identified. Economic utility (78%) and old age security (61%) was found to be the major reasons most families has quoted in preferring a son. Conclusions: By improving the literacy rate and job opportunities in the community, fertility rate can be reduced, especially in rural areas where the other options are limited.